First-ever community-level anticipatory action simulation for drought hazard in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj (International Water Management Institute, 2024)
The Drought Anticipatory Action (AA) Simulation was conducted in Ellawewa Grama Niladhari Division (GND) within the Anuradhapura district of Sri Lanka to enhance community preparedness and resilience against drought hazards. This simulation aimed to equip communities with an AA framework for mitigating the adverse effects of drought through structured preparedness, readiness, and activation phases. Key objectives included improving existing drought management systems, fostering long-term adaptability, and raising awareness of disaster risk reduction strategies. The simulation activities were designed around specific triggers derived from forecast and monitoring indicators, ensuring timely and effective responses tailored to the local context. The preparedness phase focused on water conservation, water infrastructure repair, and food preservation, while the readiness phase emphasized livestock management, adaptive agricultural practices, and resource stockpiling. The activation phase implemented immediate interventions, including livestock relocation, water distribution, and community health monitoring. The simulation employed inclusive criteria to prioritize vulnerable groups, adhering to principles of Gender Equality and Social Inclusion (GESI) and considering low-income households and families with disabilities. This targeted approach ensured equitable participation and addressed marginalized populations' unique challenges. The simulation provided a comprehensive platform to test and refine drought anticipatory action protocols by integrating proactive measures with community engagement. The AWARE initiative strengthened community readiness, promoted sustainable agricultural practices, and improved access to forecast data, enabling informed decision-making. The exercise highlighted the importance of timely interventions and a proactive approach to disaster mitigation.